Headaches attributed to cranial and cervical artery dissections - Diana Doukhi; Stéphanie Debette; Jérome Mawet (The Journal of Headache and Pain)
Abstract Headache is a common neurological symptom, often leading to the investigation of secondary causes, including cerebrovascular conditions such as cranial and cervical artery dissection (CCAD). CCAD, a significant cause of stroke in younger adults, commonly presents with headache or neck pain, isolated or accompanied by neurological deficits, and may mimic primary headache disorders, complicating timely diagnosis. This review explores the role of headache in CCAD, specifically addressing headache as an initial presentation, its evolution post-dissection, and as a potential risk factor of CCAD. By synthesizing current evidence, the review aims to improve early detection and clinical management of CCAD in headache patients.